(untitled) (Revista Iberoamericana de Bioética, 2021)
This is an analysis of the connections between Buddhist ethics and bioethics based on an integrative literature review that applied the keywords “Bioethics”, “Buddhism” and “Health”. 17 articles that met the inclusion criteria and whose contents brought together varied themes such as cultural differences, end-of-life issues and abortion were analysed. It was found that Buddhist ethics emphasizes compassion and interrelationships as the basis for health-related actions, offering bioethics a powerful interdisciplinary and intercultural framework for resolving contemporary ethical conflicts involving individual, collective, and global health.